Reorientasi Tujuan Pemidanaan Dalam Sistem Peradilan Pidana Indonesia: Analisis Penologi Antara Pendekatan Retributif Dan Restoratif - Nadia Permata Sari; Muhammad Aldiffo Widyoza; Yelse Maya Wulandari; Tia Zahara; Renindita . (GLOBAL SCIENTS PUBLISHER, 2026)
This study aims to examine the dynamics of sentencing theory development from a penological perspective, while assessing the relevance of retributive and restorative approaches in achieving punishment objectives grounded in justice, utility, and offender rehabilitation in Indonesia. The normative legal method is employed, utilizing statutory and conceptual approaches. The analysis reveals a paradigm shift from a retribution-centered model toward an integrative framework accommodating deterrence, rehabilitation, and restoration. This transformation is reflected in the sentencing objectives stipulated under Law Number 1 of 2023 on the Criminal Code, the application of restorative justice mechanisms pursuant to Prosecutor Regulation Number 15 of 2020, and the reinforced correctional functions under Law Number 22 of 2022. The retributive approach retains significance in upholding legal certainty and preserving the public sense of justice, particularly in serious criminal cases. The restorative approach, meanwhile, contributes to repairing the relationships among offenders, victims, and communities, and strengthens social reintegration. Indonesia's sentencing system accordingly demonstrates an integrative orientation that seeks to balance legal certainty, social utility, and respect for human dignity.